Nationalism ideology in Malaysia islamic movements - Mohamad Kamil, Ibrahim Majdi (GADING Journal for the Social Sciences, 2025)
This article will focus on the role of Islamic movements in Malaysia in fostering nationalism ideology. The early movement of the nationalism ideology in Malaysia based on Islamic values was spearheaded by a movement called Kaum Muda. The Kaum Muda movement was influenced by figures and reading materials from the Middle East. They brought a reform ideology also called Tajdid or Islah. This writing analyses the development of the reform nationalism ideology based on Islamic values. The results of this found the nationalism ideology brought by Kaum Muda movements and have developed even after independence during the Islamic revival in different groups. Even though the Kaum Muda movement group was only active during the colonisation era, the reform nationalism ideology by Kaum Muda developed after independence with a similar objective.